A Single and Multiple Ascending Dose Study of Toll‐Like Receptor 7 Agonist (RO7020531) in Chinese Healthy Volunteers. Issue 5 (14th May 2020) - Luk, Andrea; Jiang, Qiudi; Glavini, Katerina; Triyatni, Miriam; Zhao, Na; Racek, Tomas; Zhu, Yonghong; Grippo, Joseph F.
Abstract : Toll‐like receptor 7 (TLR7) agonists modulate broad spectrum immune activity and are evaluated in the treatment of human diseases, including cancer and chronic viral infection. RO7020531, an oral prodrug of a TLR7 agonist, is in clinical development as part of a curative regimen against chronic hepatitis B. We report the safety, tolerability, pharmacokinetics (PKs), and pharmacodynamics (PDs) of RO7020531 in healthy Chinese volunteers following single and multiple ascending doses (SAD and MAD). PK and PD samples were evaluated from four SAD cohorts and 3 MAD cohorts with 10 subjects each (8 active and 2 placebo). Safety and tolerability were monitored throughout the study. A total of 155 adverse events (AEs) were reported in 49 subjects. Fifty‐one AEs in 18 subjects were assessed as treatment‐related. Most of the AEs were mild; nine subjects experienced moderate AEs; there were no severe AEs. In two 150 mg MAD cohorts given every other day (q.o.d.), 7 of 20 subjects experienced pyrexia and were discontinued due to transient asymptomatic lymphopenia, which resolved 24–48 hours postdose. The PK of the active metabolite, RO7011785, increased linearly with dose from 40 mg to 170 mg. There was no PK accumulation following q.o.d. dosing. The PK profile is consistent with observations in white subjects in the global first‐in‐human study. SADs and MADs of RO7020531 resulted in dose‐dependent increases in TLR7 response markers at 100 mg or above. Flu‐like symptoms were associated with higher interferon‐α levels. RO7020531 was safe and acceptably tolerated in healthy Chinese volunteers with a multiple 150 mg q.o.d. dose regimen.